PENGEMBANGAN HANDOUT DILENGKAPI GAMBAR DAN PETA KONSEP PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA UNTUK SMP - Yanti, Rina Nofrika; Sudirman, Sudirman; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
ABSTRACT Learning process that have done by teacher be providing can reactived the students to learn and develop the various potential in themselves. To achieve the learning goals that be providing, needs a media that can help teachers to deliver the information of lesson materials to students. Either of the learning media that can use by teachers are using lesson materials. The lesson materials that usually used in learning proses of biology class VIII in SMP N 1 Koto XI Tarusan is textbooks. The book was unattractive, the picture in the book was uncommunicative, has not complete and still black-white colours. Related to them, the lesson materials can be provide in handout form were complete with picture and concept map in the materials circulatory system of humans. This research have to produce handout that complete with picture and concept map were valid and practical of the materials of human circulatory system. This research is development research with a procedural model of 4D models. This research only made with three phase, that is define, design and develop. This research made in college of STKIP PGRI West Sumatra and SMPN 1 Koto XI Tarusan class VIII semester of academic year 2013/2014. The subjects of this research consisted of 4 validator , and to test the practicalities done by 2 teachers and 20 students. The data of this reseach is primary data from questionnaires validity and practicalities, then analyzed with descriptive analysis. The results of data analysis showed that average value of validity handout complete with pictures and concept maps resultant that is 88.78 % categorized valid. The results of test analysis practicalities handout with pictures and concept map by teachers with average value 93.05 % with very practically category, whereas the average value of students practically are 88.22 % with very practically category. Based on the research that have done, it can be conclud that handout complete with pictures and concept map of the matterial of human circulatory system for junior high school students who meet the criteria for a valid result and very practically.